Strength and Cost Analysis of New Steel Sets as Roadway Support Project in Coal Mines - Qinghai Li; Renshu Yang; Jingkai Li; He Wang; Zhijie Wen (Advances in Materials Science and Engineering)
Roadway support in swelling soft rocks in coal mines has become a critical challenge in recent years. For deformation control in swelling soft rocks, high strength sets are preferred in sites. But high strength always means high costs. Therefore, higher strength sets with not too much cost will be more welcomed in situ. Based on this, three new sets, including a floor beam set, a roof + floor beams set, and a roof + floor beams + braces set, have been developed in the present research. Strength comparisons and costs comparisons have been conducted in this research. Results illustrate that compared with the original set, in the floor beam set, the relative strength of bottom corners reaches 2.964, while the relative cost reaches 1.294; compared with the original set, in the roof + floor beams set, the relative strength of the top arch reaches 2.345, while the relative strength of bottom corners reaches 2.964, and the relative cost reaches 1.568; and compared with the original set, in the roof + floor beams + braces set, the relative strength of the top arch reaches 2.635, and the relative strength of bottom corners reaches 5.905, but the relative cost reaches 1.930. Floor beam set and roof + floor beams set illustrate higher strength and not too higher costs than the original set. Although the roof + floor beams + braces set exhibit much higher strength, they also demonstrate much higher costs than the original set. These new sets can be chosen according to different geological conditions in situ.